Tumor Differentiation is the Dominant Prognostic Factor for Patients with Colorectal Neuroendocrine Neoplasms with Distant Metastasis - Zhijie Wang; Susheng Shi; Hongchang Ren; Qian Liu (International Journal of Endocrinology)
Purpose. Colorectal neuroendocrine neoplasms (NENs) are rare tumors. The prognosis and prognostic factors of metastatic colorectal NENs have not been fully elucidated. Methods. We retrospectively enrolled 77 consecutive patients diagnosed with colorectal NENs with synchronous distant metastases between 2000 and 2021. All patients were assigned to the neuroendocrine tumor (NET) group or the neuroendocrine carcinoma (NEC) group based on histological differentiation. Propensity score matching (PSM) was performed to minimize confounding bias. The Kaplan–Meier method was used to calculate the survival rates. Univariate and multivariate logistic regression analyses were performed to identify prognostic factors. Results. In total, 35 (45.5%) and 42 (54.5%) patients had well-differentiated NETs and poorly differentiated NECs, respectively. The median overall survival (OS) was 26 months for the entire cohort, and the 1-year, 3-year, and 5-year OS rates were 69.4%, 41.4%, and 27.8%, respectively. In the subgroup analysis, the median OS was 62 and 10 months for NETs and NECs, respectively. Univariate analysis demonstrated that patients with a primary tumor located in the colon, ulcerative tumors and poorly differentiated tumors were at higher risk for poorer progression-free survival (PFS) and OS. However, only histological differentiation was identified as an independent factor affecting OS (hazard ratio (HR) = 8.28, 95% confidence interval (CI): 2.98–23.01, P<0.001) in multivariate analysis. After PSM, histological differentiation was further confirmed as the dominant factor affecting OS (HR = 6.09, 95% CI: 1.96–18.95, P=0.002)). Conclusion. Histological differentiation was the most dominant prognostic factor in patients with metastatic colorectal NENs. Patients with well-differentiated NETs had a good chance of long-term survival.